Management of Learning Tahsin Qur’an - Julaeha, Siti; Hambali, Adang; Erihadiana, Mohamad; Hapid, Hapid (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This research is motivated by several problems, both personal and global, including lack of clear strategies and methods, low student involvement, effective assessment and feedback, limited resources, the use of technology in learning the Qur'an, advances in science and technology, democratization and moral decadence. So that Islamic education needs to take strategic steps by fixing several internal problems. In essence, Islamic educational institutions must prepare superior human resources who have competitiveness in the face of global competition, so that the management of Qur'anic tahsin learning becomes very important for educational institutions, especially Islamic boarding schools, to be mastered and implemented by every educational institution. The main objectives of this study are to identify the management of Tahsin Al-Qur'an learning in educational institutions, especially in Al-Qur'an Islamic boarding schools in West Java, namely: 1) analyze the learning planning of Tahsin Al-Qur'an in Pesantren Al-Qur'an in West Java, 2) analyze the implementation of learning Tahsin Al-Qur'an in Pesantren Al-Qur'an in West Java, 3) analyze the results in learning Tahsin Al-Qur'an in the Islamic Boarding School of the Qur'an exist in West Java, 4) analyze supporting and inhibiting factors in learning Tahsin Al-Qur'an in the Qur'an Islamic Boarding School in West Java. The approach used in this study is descriptive qualitative research which is a response to the presence of something about human existence, not only to understand specific or particular, but all aspects. The results of this study show that Based on the results of a study entitled "Management of Tahsin Al-Qur'an Learning (Pesantren Research in West Java)" it can be concluded that each Islamic boarding school institution has different learning models, learning strategies and ways of evaluating and has different graduation standards so that it has characteristics, pesantren are different even though the same educational institutions are Tahsin al Qur'an pesantren and not all pesantren have management of learning